Generalized Representation of Stereoscopic Surface Shape and Orientation in the Human Visual Cortex - Li, Zhen; Shigemasu, Hiroaki (Frontiers in Human Neuroscience, 2019)
The brain’s ability to extract three-dimensional (3D) shape and orientation information from viewed objects is vital in daily life. Stereoscopic 3D surface perception relies on binocular disparity. Neurons selective to binocular disparity are widely distributed among visual areas, but the manner in these areas are involved in stereoscopic 3D surface representation is unclear. To address this, participants were instructed to observe random dot stereograms depicting convex and concave curved surfaces and the blood oxygenation level-dependent signal of visual cortices was recorded. Two surface types were (i) horizontally positioned surfaces defined by shear disparity and (ii) vertically positioned surfaces defined by compression disparity. The surfaces were presented at different depth positions per trial. Functional magnetic resonance imaging data were classified from early visual areas to higher visual areas. We determined whether cortical areas were selective to shape and orientation by assessing same-type stimuli classification accuracies based on multi-voxel activity patterns per area. To identify whether some areas were related to a more generalized sign of curvature or orientation representation, transfer classification was used by training classifiers on one dataset type and testing classifiers on another type. Same-type stimuli classification results showed that most selected visual areas were selective to shape and all were selective to the orientation of disparity-defined 3D surfaces. Transfer classification results showed that in the dorsal visual area V3A, classification accuracies for the discriminate sign of surface curvature were higher than the baseline of statistical significance for all types of classifications, demonstrating that V3A is related to generalized shape representation. Classification accuracies for discriminating horizontal–vertical surfaces in higher dorsal areas V3A and V7 and ventral area lateral occipital complex as well as in some areas of intraparietal sulcus were higher than the baseline of statistical significance, indicating their relation to the generalized representation of 3D surface orientation.